Keseimbangan antara Pemanfaatan dan Kelestarian: Alih Fungsi Hutan menjadi Ladang Jagung Di Kabupaten Bima - Afida Dwi Nurjannah; Muhammad Sarjan (Lembaga Bale Literasi, 2025)
This research aims to identify the impact of forest conversion into corn land, analyze related policies and regulations and develop recommendations for sustainable land management strategies. The method in this research was carried out using a library review method or literature study and analyzing various relevant reading materials, journals, books and documents. The limitation of this research is the conversion of forest land into corn farming land. The location of this research was carried out in Bima Regency. Land conversion in this area occurs due to unsustainable agricultural practices, increasing economic needs and lack of clear policies regarding land conversion. The results of the analysis show that the impacts resulting from the conversion of forests into corn farming in Bima Regency are deforestation, soil erosion, changes in water quality, floods and droughts as well as loss of biodiversity. Conservation efforts need to be carried out which can involve the community's active role in achieving ecosystem balance. Efforts that can be recommended are the implementation of sustainable agricultural practices such as agroforestry as well as providing education and training to the community as well as creating policies that can encourage this to achieve a balance of sustainable use and sustainability.